2005
DOI: 10.1152/japplphysiol.01190.2004
|View full text |Cite
|
Sign up to set email alerts
|

Energy cost and muscular activity required for leg swing during walking

Abstract: To investigate the metabolic cost and muscular actions required for the initiation and propagation of leg swing, we applied a novel combination of external forces to subjects walking on a treadmill. We applied a forward pulling force at each foot to assist leg swing, a constant forward pulling force at the waist to provide center of mass propulsion, and a combination of these foot and waist forces to evaluate leg swing. When the metabolic cost and muscle actions were at a minimum, the condition was considered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
117
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 134 publications
(122 citation statements)
references
References 22 publications
3
117
2
Order By: Relevance
“…Second, the normalized net joint power data were integrated over the duration of the stride cycle to calculate the work done (J kg Previous studies have demonstrated that differences exist in the metabolic cost associated with stance versus swing phase muscle actions during human walking and running, with at least 70% of the total metabolic cost attributable to stance phase muscle actions (Gottschall and Kram, 2005;Modica and Kram, 2005;Umberger, 2010). We therefore calculated all parameters of interest for stance and swing separately.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, the normalized net joint power data were integrated over the duration of the stride cycle to calculate the work done (J kg Previous studies have demonstrated that differences exist in the metabolic cost associated with stance versus swing phase muscle actions during human walking and running, with at least 70% of the total metabolic cost attributable to stance phase muscle actions (Gottschall and Kram, 2005;Modica and Kram, 2005;Umberger, 2010). We therefore calculated all parameters of interest for stance and swing separately.…”
Section: Discussionmentioning
confidence: 99%
“…They found the hip's contribution to significantly decrease (from 44% to 32%) and the ankle's contribution to significantly increase (from 39% to 47%). We have expanded upon these findings by reporting: (1) the relative contributions from each joint towards P þ tot (and W þ tot ) for stance and swing separately (given that previous studies have demonstrated that at least 70% of the total metabolic cost during locomotion is attributable to stance-phase muscle actions; Gottschall and Kram, 2005;Modica and Kram, 2005;Umberger, 2010); and (2) the relative contributions from each joint towards P À tot (and W À tot ). The relative contributions from each joint were influenced by a change in locomotion mode, especially for the hip (Fig.…”
Section: Increasing Steady-state Walking Speedmentioning
confidence: 99%
“…We analyzed and compared EMG activity for subjects while walking at their PTS during each condition. For the impeding J. L. Bartlett and R. Kram (Gottschall and Kram, 2005). The system of rubber tubing and pulleys apply forces at either the feet or near the center of mass.…”
Section: Measurement Of Muscle Activitymentioning
confidence: 99%
“…Although this is an important aspect of locomotion that ultimately cannot be ignored, we have chosen to focus on the underlying mechanisms that have a dominant influence on the energetics of whole-body trajectory management (Donelan et al, 2002a;Kuo et al, 2005). There is some evidence that swinging the leg consumes approximately 10-33% of metabolic expenditure during bipedal walking (Doke et al, 2005;Gottschall and Kram, 2005;Umberger, 2010), however the dynamics of a pendular leg (or more specifically, a double pendulum) can likely be facilitated with mostly passive dynamics.…”
Section: Leg Swing Dynamicsmentioning
confidence: 99%